2008
DOI: 10.1007/s10450-008-9145-6
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Cr (VI) from aqueous solutions by the nonliving biomass of Alligator weed: kinetics and equilibrium

Abstract: The removal of Cr (VI) from aqueous solutions using Alligator weed, a freshwater macrophyte, was investigated in batch studies. Various factors including solution pH, Cr (VI) concentrations, agitation time, and temperature were taken into account and promising results obtained. An initial solution pH of 1.0 was most favorable for Cr (VI) removal. The kinetic data were analyzed using several models, including the pseudo-second-order equation, external diffusion model, and intraparticle diffusion model. The comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 35 publications
1
20
0
1
Order By: Relevance
“…The experimental results are fitted to the Sips model (Sips 1948) which is a combined form of the Langmuir and Freundlich models and is suitable for describing heterogeneous adsorption systems at a wide range of pressures (Foo and Hameed 2010;Casas et al 2012). In the current research the Sips parameters are derived by linearizing the experimental data, as was suggested by Wang et al (2008).…”
Section: Introductionmentioning
confidence: 99%
“…The experimental results are fitted to the Sips model (Sips 1948) which is a combined form of the Langmuir and Freundlich models and is suitable for describing heterogeneous adsorption systems at a wide range of pressures (Foo and Hameed 2010;Casas et al 2012). In the current research the Sips parameters are derived by linearizing the experimental data, as was suggested by Wang et al (2008).…”
Section: Introductionmentioning
confidence: 99%
“…Cette adsorption, qui dépend du pH, est spontanée et exothermique. Les données ELISEO, 2008BARAL et al, 2008ABUL-HOSSAIN et al, 2005WANG et al, 2008 Notre étude SHARMA et FORSTER, 1994YOUNG et al, 2006 Tableau 6. Comparaison de la capacité maximale d'adsorption (q max ) du Cr (VI) sur différents adsorbants.…”
Section: Resultsunclassified
“…Pseudo-first-order and pseudo-second-order equations can be used assuming that the measured concentrations are equal to surface concentrations 13 . The pseudo-first-order rate lagergren model is 14 : dq = k 1 , ads(q e -q) dt Where, q (mg/g) is the amount of adsorbed heavy metals on the adsorbent at time t and k 1 , ads (min -1 ) is the rate constant of first-order adsorption 15 [17][18][19][20][21][22][23][24][25][26] q e the equilibrium sorption uptake, is extrapolated from the experimental data at time t = infinity. A straight line of log(q e -q) versus t suggests the applicability of this kinetic model.…”
Section: Kinetic Modeling In a Batch Systemmentioning
confidence: 99%
“…The adsorption isotherm was also fitted to Langmuir model 22 . The Langmuir equation which is valid for monolayer adsorption on to a surface is given below.…”
Section: Langmuir Modelmentioning
confidence: 99%
See 1 more Smart Citation